PRAKTIK PENGANGKATAN ANAK DI KABUPATEN PACITAN: IMPLIKASI ADMINISTRASI KEPENDUDUKAN TERHADAP PERWALIAN NIKAH DALAM PERSPEKTIF FIQH MUNAKAHAT - Doni Isroyan; Izzul Mutho` (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study analyzes child adoption practices in Pacitan Regency and its implications for marriage guardianship from a Fiqh Munakahat perspective. The primary focus is the administrative recording of adoptive parents' names in birth certificates, which potentially obscures a child's lineage (nasab). Through qualitative field research at the Pacitan Civil Registration Office, Religious Court, and Arjosari Religious Affairs Office, it was found that the Civil Registration Office employs a "marginal note" (catatan pinggir) policy to maintain the authenticity of the child's origins based on court decrees. Sociologically, legal awareness for formalizing adoption remains low in Pacitan, as most cases are handled informally due to economic or educational factors. In Fiqh Munakahat, adoption does not automatically grant marriage guardianship rights to adoptive parents; these rights remain with the biological guardian (wali nasab) as stipulated in Surah Al-Ahzab verse 5. The marginal note policy is considered a form of maslahah mursalah that upholds the principle of hifdz al-nasab for the validity of marriage under Sharia law. Keywords:  Child Adoption; Birth Certificate; Marriage Guardianship; Fiqh Munakahat; Pacitan Regency.